Deteksi Dini dan Tatalaksana Rheumatoid Arthritis - Farhry Alvini Rahmania; Sibero, Hendra Tarigan; Ramadhian, Muhammad Ricky (Medula, 2024)
Rheumatoid arthritis (RA) is a long-term progressive inflammatory autoimmune disorder that can caused damage to the joints into disability, if it isn’t handled appropriately. There are 1.4 million people in Indonesia that have been found to suffer from rheumatoid arthritis. In the early stages of rheumatoid arthritis, there are symptoms such as fatigue, flu-like syndromes, swollen joints and pain, and morning stiffness; and also increased levels of C-reactive protein (CRP) and increased sedimentation rate of erythorisite (ESR). In contrast, untreated rheumatoid arthritis displays severe systemic manifestations such as pleural effusion, pulmonary nodules and interstitial lung disease, IMF, vasculitis in small and medium arteries, re-evolution, cartilage damage, rheumatic nodules and others. Diagnosis of rheumatoid arthritis is established after assessing symptoms, physical examination, risk factor, family history, assessment along with ultrasound, and lab marker assessment such as increased levels of CRP and ESR in serum and detection of RA-specific autoantibodies. Rheumatoid arthritis is incurable, but it can be controlled with appropriate medication and prognosis monitoring. The prognosis of rheumatoid arthritis is based on clinical evidence and laboratory examination. Early detection and appropriate management of rheumatoid arthritis are key to better prognosis. This article therefore discusses the importance of early diagnosis and treatment of rheumatoid arthritis.